Збалансований економічний розвиток територій в умовах забезпечення стабільності управління людськими ресурсами - Bantash, Anastasiia; Koval, Viktor; Bashynska, Maryna; Kozlovtseva, Valentyna (Dr. Viktor Koval, 2020)
Introduction. Reforming the territorial organization of power on the principles of decentralization is one of the key areas of systemic social transformation in Ukraine. The development of a country is impossible without the development of its regions and depends on how effective and efficient is the management of human resources at the regional and local levels, which act as an economic resource and ensure its social integrity and capacity to implement reforms at the regional level. Aim and tasks. The purpose of this article is to study the impact of decentralization reforms in Ukraine, in particular its impact on management efficiency and ensuring the stability of human resources development for the balanced development of territorial socio-economic systems. Results. The paper considers theoretical and practical issues of decentralization as a process that is currently taking place in Ukraine. Emphasis is placed on the fact that decentralization should become a development factor for social, cultural, economic, financial, environmental and other systems, and through these systems a development factor for citizens. At the regional level, it is within the territorial socio-economic systems that human potential is concentrated and human resources are reproduced, which are a source of competitive advantage. Conclusions. The lack of rational zoning of territories and a balanced administrative-territorial structure is due to the lack of effective regional management, which should be based on the use of improved organizational and economic mechanisms for the development of administrative-territorial units. In conditions when human resources were considered not as a factor of production, but as an important resource for achieving the goals of the organization, uniting the interests of representatives of united territorial communities becomes the main principle of reproduction of human resources and balanced development of territories. To achieve the self-sufficiency of local self-government, a number of objective and subjective dangers of the development of undesirable political consequences are currently hindered. The decisive factor in overcoming the negative processes in the economy and social life of the country is the formation of personnel policy in a decentralized government, as the ability of government to manage effectively depends on the professional level of its managers.